2015
DOI: 10.3389/feart.2015.00086
|View full text |Cite
|
Sign up to set email alerts
|

MSP-Tool: A VBA-Based Software Tool for the Analysis of Multispecimen Paleointensity Data

Abstract: The multispecimen protocol (MSP) is a method to estimate the Earth's magnetic field's past strength from volcanic rocks or archeological materials. By reducing the amount of heating steps and aligning the specimens parallel to the applied field, thermochemical alteration and multi-domain effects are minimized. We present a new software tool, written for Microsoft Excel 2010 in Visual Basic for Applications (VBA), that evaluates paleointensity data acquired using this protocol. In addition to the three ratios (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…We used four field levels (15, 30, 45 and 60 μT) and three specimens per field level. Data were analysed using MSP-Tool for MS Excel 2010 (Monster et al, 2015b) and its built-in reliability criteria. If the average alteration ε alt between the first and fourth heating step exceeded 3% (de Groot et al, 2013) and/or if the intersection with the y-axis of the linear fit in the domain-statecorrected plot was not within error of its theoretically prescribed value of (0, −1) (Fabian and Leonhardt, 2010), the result from the original method (MSP-DB; Dekkers and Böhnel, 2006) was preferred.…”
Section: Sitementioning
confidence: 99%
See 1 more Smart Citation
“…We used four field levels (15, 30, 45 and 60 μT) and three specimens per field level. Data were analysed using MSP-Tool for MS Excel 2010 (Monster et al, 2015b) and its built-in reliability criteria. If the average alteration ε alt between the first and fourth heating step exceeded 3% (de Groot et al, 2013) and/or if the intersection with the y-axis of the linear fit in the domain-statecorrected plot was not within error of its theoretically prescribed value of (0, −1) (Fabian and Leonhardt, 2010), the result from the original method (MSP-DB; Dekkers and Böhnel, 2006) was preferred.…”
Section: Sitementioning
confidence: 99%
“…If the average alteration ε alt between the first and fourth heating step exceeded 3% (de Groot et al, 2013) and/or if the intersection with the y-axis of the linear fit in the domain-statecorrected plot was not within error of its theoretically prescribed value of (0, −1) (Fabian and Leonhardt, 2010), the result from the original method (MSP-DB; Dekkers and Böhnel, 2006) was preferred. Data points that were outside the bootstrapped confidence interval (Monster et al, 2015b) that was initially produced based on the results of all measured samples were rejected and the data were reinterpreted omitting these data points.…”
Section: Sitementioning
confidence: 99%
“…Out of the 30 ARM-tests done, nine were successful; MSP-DSC experiments were carried out for these nine combinations of site and temperature. The MSP results were interpreted using MSP-Tool (Monster et al 2015). To deem the outcome of a MSP-DSC experiment reliable, the alteration induced during the experiment should be minimal: we therefore reject samples with |ε alt | > 5 per cent; and only accept sites that produce an average ε alt for all samples included in the interpretation between -3 and 3 per cent.…”
Section: Multispecimen Techniquementioning
confidence: 99%
“…Biasing effects induced by pTRM tails are minimized by aligning the specimens' NRMs parallel to the field in the oven. The data analysis was performed using a MSP-TOOL software of Monster et al (2015) and are reported in Table 2 while some representative determinations are presented in Fig. 7.…”
Section: Sample Sr12-7mentioning
confidence: 99%
“…Multispecimen (MSP-DB) vs. FC (fraction corrected) and MSP-DSC (domain state corrected afterFabian and Leonhardt, 2010) absolute intensity determination (MSP-TOOL ofMonster et al, 2015).…”
mentioning
confidence: 99%